Lake sludge-based unfired wetland ceramsite substrate and preparation method thereof

By using lake silt and industrial waste to prepare non-fired wetland ceramsite matrix, the problems of resource waste and environmental pollution in lake silt treatment are solved. This achieves efficient and low-cost ceramsite production, which is suitable for soil improvement and building materials, and improves the permeability of wetland ecological environment and plant growth conditions.

CN119263712AActive Publication Date: 2025-01-07SAFECLEEN TECH
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411336227.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-07
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

Existing technologies for treating lake sludge present problems such as resource waste, environmental pollution, and high energy consumption. Traditional ceramsite production uses non-renewable raw materials and has a complex preparation process. Existing non-fired ceramsite has low strength and poor water resistance, making it difficult to achieve industrialization.

Method used

Using industrial wastes such as lake silt, slag, and fly ash as raw materials, wetland ceramsite matrix is ​​prepared through a non-fired process. Sodium hydroxide solution is used to activate the gelation reaction, forming a dense structure, and spherical ceramsite is prepared to improve strength and air permeability.

Benefits of technology

It achieves environmentally friendly resource reuse, reduces energy consumption and production costs, and produces high-performance ceramsite matrix suitable for soil improvement and building materials, improving the permeability of wetland ecosystems and plant growth conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263712A_ABST
    Figure CN119263712A_ABST
Patent Text Reader

Abstract

The invention provides a lake sludge-based unfired wetland ceramsite substrate and a preparation method thereof. The ceramsite substrate is prepared from the following raw materials in parts by mass: 55 to 65 parts of mud cake, 10 to 30 parts of slag, 10 to 30 parts of fly ash, 3 to 7 parts of sodium hydroxide solution and water. The ceramsite substrate is prepared by the following steps: S1, proportioning: drying, crushing and grinding a prepared mud cake to obtain mud powder; s2, mixing the materials to prepare a mud pie; s3, preparing ceramsite green pellets; s4, carrying out steam curing on the ceramsite green balls in the step 3 to obtain ceramsite with pores; and S5, carrying out water retention and natural curing on the ceramsite to obtain the ceramsite substrate. The ceramsite matrix prepared by the invention takes lake dredged sludge as a main raw material and industrial wastes such as fly ash and slag as auxiliary materials, is green and environment-friendly, is reasonable in cost, not only realizes effective recycling of resources, but also can reduce energy consumption, forms an environment functional material with a water purification effect, achieves the effect of treating wastes with wastes, and achieves multiple purposes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of environmental functional materials, and in particular to a lake sludge-based unburned wetland ceramsite matrix and a preparation method thereof. Background Art

[0002] In recent years, various places have carried out dredging work, generating a large amount of dredged sludge. These sludges have high water content, large volume, low strength, and may contain toxic and harmful substances such as organic matter and heavy metals. If not handled properly, they are very likely to cause secondary pollution. At present, common sludge treatment methods mainly include dewatering and landfilling, land utilization and building material utilization. In the context of emphasizing green and low-carbon development, the importance of rational resource utilization of dredged sludge has become increasingly prominent. Traditional dewatering and landfilling methods require a large amount of land resources, while land utilization has the risk of causing secondary pollution to the environment. Therefore, using sludge as building materials can not only achieve reduction and harmless treatment, but also effectively reuse resources.

[0003] Ceramic granules are an important building material. Due to their low apparent density, more pores, and higher mechanical properties, they are light, corrosion-resistant, and frost-resistant. At the same time, they have a rough and porous surface and are widely used in many fields such as construction and gardening. However, the main raw materials for the production of traditional ceramsite, clay and shale, are non-renewable resources and have been banned or restricted from mining. Therefore, it is imperative to seek a new type of environmentally friendly ceramsite to replace traditional ceramsite containing clay and shale.

[0004] The main components of silt and sand include silicate minerals such as quartz, feldspar, mica, kaolinite, montmorillonite, and illite. Its main chemical component is Al 2 O 3 and SiO 2 Similar to the raw materials for preparing ceramsite, it has attracted widespread attention from many scholars. However, most ceramsite used in the field of building materials has high strength requirements and requires high-temperature sintering. It has disadvantages such as complex pretreatment process, high energy consumption, and serious pollution. The existing unfired ceramsite is prone to low strength and poor water resistance during use, making it difficult to achieve true industrialization. In addition, some researchers have tried to use natural raw materials such as kaolin and bentonite to prepare artificial wetland ceramsite matrix by sintering, but there are also problems such as high cost and high energy consumption.

[0005] Therefore, there is an urgent need to develop an environmentally friendly, high-performance and cost-effective lake sludge-based unburned wetland expanded clay matrix and its preparation method, so as to achieve the green and comprehensive utilization of various wastes, turn waste into treasure, and better apply it to the field of wetland matrix. Summary of the invention

[0006] In view of this, the present invention proposes a technical solution for preparing wetland expanded clay matrix by using lake dredged sludge as the main raw material to replace clay, and using fly ash, slag and other industrial waste as auxiliary materials in a combustion-free manner.

[0007] On the one hand, the present invention provides a lake silt-based unburned wetland ceramsite matrix, which includes the following constituent raw materials in parts by mass: 55 to 65 parts of mud cake, 10 to 30 parts of slag, 10 to 30 parts of fly ash, 3 to 7 parts of sodium hydroxide solution and water.

[0008] By adopting the above technical solution and using lake sludge, slag, fly ash and other industrial waste as raw materials, not only the impact on the environment is reduced and the effective recycling of resources is achieved, but also energy consumption can be reduced and production costs can be reduced.

[0009] Furthermore, the mud cake is lake sludge after filter pressing, and the water content of the mud cake is 35-55%.

[0010] Lake silt usually contains a large amount of organic matter, nutrients and other pollutants. If it is discharged or piled up directly without treatment, it will cause environmental pollution. Converting a large amount of silt into mud cake through filter pressing can not only effectively reduce the volume of silt, facilitate transportation and storage, but also make it easier to carry out the next step of treatment or disposal, such as drying, solidification, incineration, etc., thereby effectively reducing the cost of silt treatment and improving economic benefits. At the same time, reducing the moisture in silt through filter pressing helps control the spread of pollutants, reduces potential harm to groundwater and soil, and reduces environmental pollution.

[0011] Furthermore, the slag is of S95 grade, has a particle size of 1 to 29 μm, a median particle size D50 of 11.9 μm, and an effective component of not less than 70%.

[0012] Furthermore, the fly ash is Class F fly ash, with a particle size of 1 to 33 μm, a median particle size D50 of 9.8 μm, and an effective component of not less than 70%.

[0013] By adopting the above technical scheme, a ceramsite matrix with excellent performance, reasonable cost and environmental protection can be prepared, which is suitable for a variety of uses, such as soil improvement, building materials and other fields. The high content of effective ingredients and particle size of slag and fly ash help to improve the overall strength of the ceramsite matrix and ensure the uniformity of the mixture, making the performance of the ceramsite matrix more consistent. At the same time, the fine particles can also fill the gaps, reduce the porosity, and increase the density of the ceramsite matrix, thereby enhancing its durability. In addition, the active ingredients of these two materials can promote the optimization of the internal structure of ceramsite and improve its physical and mechanical properties, such as compressive strength and wear resistance.

[0014] In summary, compared with the addition of cement, lime and other high-alkalinity gel-curing materials in the prior art, the lake sludge added in the present invention has more environmentally friendly raw materials and lower energy consumption in the preparation process. On this basis, it can also ensure that indicators such as strength and water absorption meet the standard requirements of relevant light aggregates. Compared with the addition of steel slag in the prior art, the slag and fly ash added in the present invention have a wide range of sources, are environmentally friendly (do not contain harmful substances, such as heavy metals, etc.), have relatively low processing costs, and can reduce the accumulation of industrial waste and realize resource recycling.

[0015] Furthermore, the mass fraction of the sodium hydroxide solution is 12.5%.

[0016] By adopting the above technical solution, sodium hydroxide, as a strong alkali, can effectively react with silicates and other mineral components in the sludge, promote the solidification process, and may help form a pore structure to a certain extent. The concentration of 12.5% ​​is sufficient to stimulate the reaction, while ensuring the reaction speed, avoiding excessively intense reactions due to excessive concentration, thereby affecting the uniformity and strength of the ceramsite matrix, and even causing unnecessary side reactions or corrosion of equipment. At the same time, at an appropriate concentration, sodium hydroxide can help form a denser and more uniform microstructure, thereby improving the physical and mechanical properties of the ceramsite matrix, such as compressive strength and durability.

[0017] Furthermore, the ceramsite matrix is ​​spherical, and the particle size is 10 to 18 mm.

[0018] By adopting the above technical solution, the gaps between the spherical ceramsite are relatively uniform, which helps to improve the air permeability and drainage of the soil, and is very beneficial to the development of plant roots, especially in wetland restoration and horticultural applications. After the spherical materials are piled up, there are many gaps inside the pile, which can better promote water penetration and light transmission and air retention, which is beneficial to the photosynthesis of plants on the substrate layer of shallow lakes and supports the attachment and growth of plants; on the contrary, the permeability is poor and the substrate is easily blocked, which in turn hinders the circulation of the water system and oxygen transmission, and is not conducive to the photosynthesis of plants and the healthy growth of the root system.

[0019] On the other hand, the present invention provides a method for preparing the above-mentioned lake sludge-based unburned wetland ceramsite matrix, the method comprising the following steps:

[0020] Step 1: Raw material pretreatment

[0021] The raw materials are prepared according to the mass fractions; the prepared mud cake is dried, crushed and ground to obtain mud powder;

[0022] Step 2: Mixing

[0023] Add the prepared slag, fly ash, sodium hydroxide solution and water to the mud powder in step 1, stir and obtain a mud mass;

[0024] Step 3: Granulation

[0025] The mud ball obtained in step 2 is formed into a ball shape and allowed to stand to obtain a ceramsite raw ball;

[0026] Step 4: Steaming and pore making

[0027] Steaming the ceramsite pellets in step 3 to obtain ceramsite with pores;

[0028] Step 5: Water conservation and maintenance

[0029] The expanded clay obtained in step 4 is naturally cured to retain water, thereby obtaining an expanded clay matrix.

[0030] By adopting the above technical scheme, industrial wastes or urban solid wastes such as lake sludge, slag and fly ash can be used to achieve resource recycling. In step one, in order to better mix, the mud cake is pretreated. The mud cake is dried, crushed and ground into fine powder through the pretreatment step, which can achieve the best mixing effect of the base material. Then, sodium hydroxide solution is added to fully cause gelling reaction and alkali excitation. If the mud cake obtained by pressure filtration is directly mixed with dry materials such as slag and fly ash, the mud cake has a water content of 35-55%, is in a block shape, has a certain plasticity, and is in a heterogeneous medium state, and the mixing effect is poor, which is not conducive to the subsequent reaction. At the same time, the preparation method can effectively form the required ceramsite structure by utilizing the characteristics of the raw materials themselves and the pore effect naturally generated during the steaming process, so that there is no need to add other additives, such as foam stabilizers and aqueous hydrogen peroxide solutions. Such a design not only simplifies the process flow, but also improves economic benefits, and reduces the use of chemicals, making the entire raw material system and even the preparation more environmentally friendly.

[0031] Furthermore, in step three, the standing time is 1 to 2 hours.

[0032] By adopting the above technical solution, the newly formed ceramsite raw balls can be initially solidified, that is, the initial setting stage. During this process, the chemical reaction in the mixture gradually begins, which helps to form a stable structure. In addition, during the static period, the water will be evenly distributed inside the ceramsite, which will help the uniform formation of pores in the subsequent steaming process, thereby improving the air permeability and drainage performance of the ceramsite.

[0033] Furthermore, in step 4, the steaming temperature is 40-60° C. and the time is 60 min.

[0034] By adopting the above technical solution, the curing reaction of ceramsite raw balls can be effectively promoted to form a uniform pore structure while maintaining the strength and stability of the ceramsite. In addition, the steam curing conditions can not only improve the performance of ceramsite, but also improve production efficiency and product quality while saving energy and reducing emissions. If steam curing is carried out under high temperature conditions, although it can accelerate the curing process, it will also increase energy consumption; if the steam curing temperature is too low, it will slow down the curing speed and affect the formation of pores, which will lead to loose internal structure of ceramsite or uneven pore distribution, resulting in poor final performance of ceramsite.

[0035] Furthermore, in step five, the water conservation curing temperature is 25 to 80° C., and the time is 7 to 14 days.

[0036] By adopting the above technical solution and carrying out water conservation curing in the temperature range of 25-80°C, the curing reaction inside the ceramsite can be further promoted, making the ceramsite structure more stable. Appropriate temperature and humidity can ensure uniform distribution of water inside the ceramsite, which helps to optimize the pore structure, thereby improving the air permeability and drainage of the ceramsite. In addition, through water conservation curing, the structure of the ceramsite is more stable, which helps to extend its service life, especially when exposed to the natural environment for a long time.

[0037] The ceramsite matrix provided by the present invention has the following beneficial effects compared with the prior art:

[0038] (1) The raw materials for preparing the ceramsite matrix of the present invention are widely available. The sludge is the product of dredging engineering treatment, and the fly ash and slag are by-products produced by coal-fired power plants and smelters, respectively. They are easy to obtain in large quantities and low in price. They can absorb a large amount of filter cakes and solid waste from industrial production produced by dredging engineering, reduce the impact on the environment, achieve effective recycling of resources, and reduce energy consumption, thereby forming an environmentally functional material with a water purification effect, achieving the effect of treating waste with waste, and achieving multiple goals at one stroke.

[0039] (2) The method for preparing ceramsite matrix of the present invention firstly adds fly ash and slag, on the one hand, utilizes the gelling reaction to exert a solidifying effect; on the other hand, during the curing process, the active oxides therein react with alkaline substances to react with calcium ions (Ca 2+ ) reacts to form hydraulic cementitious products such as CSH and CAH, thereby significantly enhancing the strength of ceramsite. In addition, blast furnace slag contains a high concentration of Mg. During the hydration process, Mg 2+ Will be like Al 3+ Replace Si 4+, to promote the formation of NA(M)-SH gel phase. The interweaving of multiple gel phases makes the microstructure of the gel phase more compact, which not only improves the strength of the ceramsite, but also enhances its corrosion resistance. Secondly, the addition of sodium hydroxide not only provides an alkaline excitation environment, but also promotes the zeolite process on the surface of the ceramsite, further improving the strength of the ceramsite.

[0040] (3) The ceramsite matrix prepared by the present invention is spherical and has a large specific surface area, which can better promote water penetration and light transmission and air retention, is beneficial to the photosynthesis of plants on the matrix layer of shallow lakes, and supports the attachment and growth of plants, so as to better improve the ecological environment of the wetland base.

[0041] (4) The ceramsite matrix prepared by the present invention is suitable for improving the bottom quality of natural wetlands such as shallow lakes, lakeside belts, wetland parks, and can also be used in artificial wetland sewage treatment matrix and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0043] Figure 1 This is a physical picture of the ceramsite matrix prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0044] The technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] The present invention is further described below in conjunction with specific examples, and the protection scope of the present invention is not limited by the following examples. The sources of the materials mainly involved in the examples are shown in Table 1 below, and the remaining materials not shown are conventional commercial products.

[0046] Table 1 Material source description

[0047]

[0048]

[0049] The following are examples of the present invention. The sludge used in the examples is from Wuhan Tangxun Lake, and its main chemical components and their mass percentages are Al 3 O 2 8~16%, SiO 2 50~70%.

[0050] Example 1

[0051] The ceramsite matrix of this embodiment is composed of raw materials and their weight parts respectively: 55 parts of mud cake, 10 parts of slag, 30 parts of fly ash, 5 parts of sodium hydroxide solution and appropriate water. The ceramsite matrix is ​​prepared by the following steps:

[0052] Step 1: Raw material pretreatment

[0053] The raw materials are prepared according to the mass fractions; the prepared mud cake is dried and crushed at 105° C., and ground with a vibration grinder for 30 seconds to obtain mud powder with a particle size of ≤0.04 mm;

[0054] Step 2: Mixing

[0055] Add the prepared slag, fly ash, sodium hydroxide solution and water to the mud powder in step 1, stir at a low speed of 140 rpm for 30 seconds, and then stir at a high speed of 285 rpm for 4 minutes and 30 seconds to obtain a mud mass;

[0056] Step 3: Granulation

[0057] The mud mass in step 2 was made into spherical balls with an average particle size of 16.2 mm by using a pelletizing machine, and then air-dried for 2 h to obtain ceramsite green balls;

[0058] Step 4: Steaming and pore making

[0059] Steaming the ceramsite pellets obtained in step 3 for 60 minutes at 40°C to obtain ceramsite with pores;

[0060] Step 5: Water conservation and maintenance

[0061] The expanded clay obtained in step 4 was naturally cured to retain water, the curing temperature was set to 25° C., and the curing time was set to 7 days to obtain an expanded clay matrix.

[0062] Example 2

[0063] The ceramsite matrix of this embodiment is composed of raw materials and their weight parts respectively: 60 parts of mud cake, 20 parts of slag, 20 parts of fly ash, 5 parts of sodium hydroxide solution and appropriate water. The ceramsite matrix is ​​prepared by the following steps:

[0064] Step 1: Raw material pretreatment

[0065] The raw materials are prepared according to the mass fractions; the prepared mud cake is dried and crushed at 105° C., and ground with a vibration grinder for 30 seconds to obtain mud powder with a particle size of ≤0.04 mm;

[0066] Step 2: Mixing

[0067] Add the prepared slag, fly ash, sodium hydroxide solution and water to the mud powder in step 1, stir at a low speed of 140 rpm for 30 seconds, and then stir at a high speed of 285 rpm for 4 minutes and 30 seconds to obtain a mud mass;

[0068] Step 3: Granulation

[0069] The mud mass in step 2 was made into spherical balls with an average particle size of 15.8 mm by using a pelletizing machine, and then allowed to stand and air-dry for 2 h to obtain ceramsite green balls;

[0070] Step 4: Steaming and pore making

[0071] Steaming the ceramsite pellets in step 3 for 60 minutes at 60°C to obtain ceramsite with pores;

[0072] Step 5: Water conservation and maintenance

[0073] The expanded clay obtained in step 4 was naturally cured to retain water, the curing temperature was set to 25° C., and the curing time was set to 7 days to obtain an expanded clay matrix.

[0074] Example 3

[0075] The ceramsite matrix of this embodiment is composed of raw materials and their weight parts respectively: 60 parts of mud cake, 30 parts of slag, 10 parts of fly ash, 5 parts of sodium hydroxide solution and appropriate water. The ceramsite matrix is ​​prepared by the following steps:

[0076] Step 1: Raw material pretreatment

[0077] The raw materials are prepared according to the mass fractions; the prepared mud cake is dried and crushed at 105° C., and ground with a vibration grinder for 30 seconds to obtain mud powder with a particle size of ≤0.04 mm;

[0078] Step 2: Mixing

[0079] Add the prepared slag, fly ash, sodium hydroxide solution and water to the mud powder in step 1, stir at a low speed of 140 rpm for 30 seconds, and then stir at a high speed of 285 rpm for 4 minutes and 30 seconds to obtain a mud mass;

[0080] Step 3: Granulation

[0081] The mud mass in step 2 was made into spherical balls with an average particle size of 16.5 mm by using a pelletizing machine, and then air-dried for 1 hour to obtain ceramsite raw balls;

[0082] Step 4: Steaming and pore making

[0083] Steaming the ceramsite pellets obtained in step 3 for 60 minutes at 50°C to obtain ceramsite with pores;

[0084] Step 5: Water conservation and maintenance

[0085] The expanded clay obtained in step 4 was naturally cured to retain water, the curing temperature was set to 25° C., and the curing time was set to 7 days to obtain an expanded clay matrix.

[0086] Example 4

[0087] The ceramsite matrix of this embodiment is composed of raw materials and their weight parts respectively: 60 parts of mud cake, 30 parts of slag, 10 parts of fly ash, 3 parts of sodium hydroxide solution and appropriate water. The ceramsite matrix is ​​prepared by the following steps:

[0088] Step 1: Raw material pretreatment

[0089] The raw materials are prepared according to the mass fractions; the prepared mud cake is dried and crushed at 105° C., and ground with a vibration grinder for 30 seconds to obtain mud powder with a particle size of ≤0.04 mm;

[0090] Step 2: Mixing

[0091] Add the prepared slag, fly ash, sodium hydroxide solution and water to the mud powder in step 1, stir at a low speed of 140 rpm for 30 seconds, and then stir at a high speed of 285 rpm for 4 minutes and 30 seconds to obtain a mud mass;

[0092] Step 3: Granulation

[0093] The mud mass in step 2 was made into spherical balls with an average particle size of 16.2 mm by using a pelletizing machine, and then air-dried for 2 h to obtain ceramsite green balls;

[0094] Step 4: Steaming and pore making

[0095] Steaming the ceramsite pellets in step 3 for 60 minutes at 60°C to obtain ceramsite with pores;

[0096] Step 5: Water conservation and maintenance

[0097] The expanded clay obtained in step 4 was naturally cured to retain water, the curing temperature was set to 25° C., and the curing time was set to 7 days to obtain an expanded clay matrix.

[0098] Example 5

[0099] The ceramsite matrix of this embodiment is composed of raw materials and their mass parts respectively: 65 parts of mud cake, 30 parts of slag, 10 parts of fly ash, 7 parts of sodium hydroxide solution and appropriate water. The ceramsite matrix is ​​prepared by the following steps:

[0100] Step 1: Raw material pretreatment

[0101] The raw materials are prepared according to the mass fractions; the prepared mud cake is dried and crushed at 105° C., and ground with a vibration grinder for 30 seconds to obtain mud powder with a particle size of ≤0.04 mm;

[0102] Step 2: Mixing

[0103] Add the prepared slag, fly ash, sodium hydroxide solution and water to the mud powder in step 1, stir at a low speed of 140 rpm for 30 seconds, and then stir at a high speed of 285 rpm for 4 minutes and 30 seconds to obtain a mud mass;

[0104] Step 3: Granulation

[0105] The mud mass in step 2 was made into spherical balls with an average particle size of 16.5 mm by using a pelletizing machine, and then air-dried for 2 h to obtain ceramsite raw balls;

[0106] Step 4: Steaming and pore making

[0107] Steaming the ceramsite pellets in step 3 for 60 minutes at 60°C to obtain ceramsite with pores;

[0108] Step 5: Water conservation and maintenance

[0109] The expanded clay obtained in step 4 was naturally cured to retain water, the curing temperature was set to 25° C., and the curing time was set to 7 days to obtain an expanded clay matrix.

[0110] The following are comparative examples of the present invention.

[0111] Comparative Example 1

[0112] The ceramsite matrix of this comparative example has the following raw materials and their weight percentages: 60 parts of mud cake, 40 parts of fly ash, 5 parts of sodium hydroxide solution and appropriate amount of water. The preparation steps are the same as those in the above embodiment.

[0113] Comparative Example 2

[0114] The ceramsite matrix of this comparative example is composed of raw materials and their weight proportions respectively: 60 parts of mud cake, 40 parts of slag, 5 parts of sodium hydroxide solution and appropriate amount of water. The preparation steps are the same as those in the above embodiment.

[0115] The ceramsite matrix prepared in the above Examples 1 to 5 and Comparative Examples 1 to 2 was tested according to the relevant records in GB17431.1-2010 "Lightweight aggregate and test methods thereof", and the performance test results shown in Table 2 were obtained.

[0116] Table 2 Performance test results

[0117]

[0118] It can be seen from the performance test results in Table 2 that the cylinder pressure strength, bulk density, 1h water absorption rate and softening coefficient of the ceramsite matrix prepared in the embodiment all meet the standard requirements, which shows that the prepared ceramsite matrix has high mechanical strength, good bulk density performance, waterproof performance and can still maintain high strength after being immersed in water.

[0119] From the test results of cylinder pressure strength, it can be seen that the raw materials of comparative example 1 do not contain slag, and its bulk density is 685kg / m 3 The density grade is 700. According to the standard of light aggregate, the corresponding cylinder pressure strength should be 3MPa or above, while the cylinder pressure strength of comparative example 1 is only 1.08MPa; fly ash is not added to the raw materials of comparative example 2, and its bulk density is 828kg / m 3 , the density grade is 900, and the corresponding cylinder pressure strength should be 5MPa or above, while the cylinder pressure strength of comparative example 1 is only 2.73MPa; it can be seen that the strength of the ceramsite matrix prepared by both does not meet the standard requirements. This is because: the active ingredients in slag (such as silicates, aluminates, etc.) and fly ash contain a large amount of active ingredients (such as silicon dioxide, aluminum oxide) that can react with alkaline substances during the curing process to generate hydraulic cementitious products such as CSH and CAH, thereby enhancing the strength of ceramsite. The combination of the two can further obtain a ceramsite matrix with higher strength.

[0120] From the test results of 1h water absorption rate, the 1h water absorption rate of the ceramsite matrix prepared by Examples 1 to 5 is 1.08% to 6.87%, and the water absorption rate of all examples is relatively low; the raw materials of Comparative Example 1 do not add slag, and its water absorption rate is 14.72%, which is much higher than that of the examples; the raw materials of Comparative Example 2 do not add fly ash, and its water absorption rate is 1.08%. Although the water absorption rate is relatively low, it has no obvious advantage over the examples. This is because: the fine particles in fly ash help to form more pores, but these pores may be relatively open, resulting in a higher water absorption rate. Therefore, when fly ash is used alone, it may not be enough to completely close the pores, thereby making the water absorption rate of ceramsite higher. The active ingredients in slag help to close the pores and form a denser structure, thereby significantly reducing the water absorption rate. Therefore, it can be considered that: when fly ash and slag are used together, the active ingredients in the two complement each other, can form a more uniform and dense pore structure, close the pores, reduce water penetration, and thus significantly reduce the water absorption rate of ceramsite.

[0121] In addition, it can be seen from Table 2, Example 2 and Example 3 that the ratio of slag to fly ash in Example 2 is 1:1, while the ratio of slag to fly ash in Example 3 is 3:1, and the water absorption rate of Example 3 in the table is significantly lower than that of Example 2. This is because the active ingredients (such as silicates and aluminates) in the slag react with alkaline substances during the curing process to form stable hydraulic products, which help to close the pores inside the ceramsite, thereby reducing the water absorption rate; the increase of slag helps to form a more compact structure, thereby reducing the chance of water infiltration. However, in combination with Comparative Example 2, the proportion of slag in Comparative Example 2 is increased to 40 parts, and no fly ash is added. From the perspective of water absorption, it is equivalent to Example 3 and has no obvious advantage; however, when purchasing materials on the market, the price of fly ash is much lower than that of slag. If only slag is used, the production cost of the ceramsite matrix will increase, and the strength of the ceramsite matrix prepared by Comparative Example 2 is not up to standard. It can be seen that the ceramsite matrix prepared by the present invention is not only excellent in performance and environmentally friendly, but also has reasonable cost, and has significant economic benefits when put into large-scale production.

[0122] Combining Example 3 and Example 4, it can be seen that the sodium hydroxide solution provides an alkaline environment for the matrix material, which helps the active ingredients in fly ash and slag to undergo hydration reactions and generate hydraulic gelling products such as CSH and CAH. These products help to seal the pores inside the ceramsite, reduce the penetration of water, and thus reduce the water absorption rate. And the more sodium hydroxide solution is used, the stronger the alkaline environment provided, the more fully the hydration reaction is promoted, the more gelling products are generated, and the better the pore sealing effect. Therefore, the water absorption rate in Example 3 will be lower than that in Example 4. In Example 5, the amount of sodium hydroxide used reaches 7 parts, but its water absorption rate is higher than that of Example 3. The inventors analyzed that the possible reasons are: in addition to the increase in the amount of mud cake in Example 5, its components can form a certain pore structure, resulting in an increase in water absorption, it may also be affected by the increase in the amount of sodium hydroxide. The increase in the amount of sodium hydroxide will cause the water absorption to change. The gel product obtained by the initial reaction can close the pores, although it affects the air permeability and drainage of the ceramsite, but can reduce the water absorption of the ceramsite matrix. However, further increasing the sodium hydroxide solution may destroy the pore structure inside the ceramsite, resulting in uneven pore distribution, which ultimately increases the water absorption of the ceramsite matrix.

[0123] From the test results of the softening coefficient, it can be seen that the softening coefficient of the comparative example 1 is significantly lower than that of the example when slag is not added to the raw materials, indicating that the water resistance of the ceramsite is poor when only fly ash is used; the softening coefficient of the comparative example 2 is comparable to that of the example when fly ash is not added to the raw materials. This is because the active ingredients in the slag help to form a denser structure, reduce the chance of water penetration, and thus improve the softening coefficient.

[0124] In summary, in the formula for preparing the ceramsite matrix of the present invention, the addition of fly ash and slag not only provides the active oxides required for the gelling reaction, but also reacts with alkaline substances during the curing process to generate hydraulic gelling products such as CSH and CAH, thereby significantly enhancing the strength of the ceramsite. The higher cylinder pressure strength and softening coefficient in the embodiment indicate that these components play an important role; and the addition of sodium hydroxide not only provides an alkaline excitation environment, but also promotes the zeolite process on the surface of the ceramsite, further improving the strength and water resistance of the ceramsite. The data in the embodiment show that the use of sodium hydroxide helps to form a more stable structure.

[0125] In addition, the method for preparing the ceramsite matrix of the present invention, the setting of the stirring, steaming and curing conditions, not only ensures the uniform mixing of the raw materials, helps to form a more uniform pore structure, but also helps the solidification reaction to form a stable structure, so as to improve the strength and water resistance of the ceramsite.

[0126] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A lake sludge-based, unburned wetland ceramsite matrix, characterized in that: The ceramsite matrix comprises the following raw materials by weight: 55-65 parts of mud cake, 10-30 parts of slag, 10-30 parts of fly ash, 3-7 parts of sodium hydroxide solution and water.

2. The lake silt-based unburned wetland ceramsite matrix according to claim 1, characterized in that: The mud cake is lake sludge after filter pressing, and the water content of the mud cake is 35-55%.

3. The lake silt-based unburned wetland ceramsite matrix according to claim 1, characterized in that: The slag is of S95 grade, has a particle size of 1 to 29 μm, a median particle size D50 of 11.9 μm, and an effective component content of not less than 70%.

4. The lake silt-based unburned wetland ceramsite matrix according to claim 1, characterized in that: The fly ash is F-type fly ash, with a particle size of 1 to 33 μm, a median particle size D50 of 9.8 μm, and an effective component of not less than 70%.

5. The lake silt-based unburned wetland ceramsite matrix according to claim 1, characterized in that: The mass fraction of the sodium hydroxide solution is 12.5%.

6. The lake silt-based unburned wetland ceramsite matrix according to claim 1, characterized in that: The ceramsite matrix is ​​spherical, and the particle size is 10 to 18 mm.

7. A method for preparing the lake sludge-based unburned wetland ceramsite matrix according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: Step 1: Raw material pretreatment The raw materials are prepared according to the mass fractions; the prepared mud cake is dried, crushed and ground to obtain mud powder; Step 2: Mixing Add the prepared slag, fly ash, sodium hydroxide solution and water to the mud powder in step 1, stir and obtain a mud mass; Step 3: Granulation The mud ball obtained in step 2 is formed into a ball shape and allowed to stand to obtain a ceramsite raw ball; Step 4: Steaming and pore making Steaming the ceramsite pellets in step 3 to obtain ceramsite with pores; Step 5: Water conservation and maintenance The expanded clay obtained in step 4 is naturally cured to retain water, thereby obtaining an expanded clay matrix.

8. The method according to claim 7, characterized in that In step 3, the standing time is 1 to 2 hours.

9. The method according to claim 7, characterized in that In step 4, the steaming temperature is 40-60° C. and the time is 60 min.

10. The method according to claim 7, characterized in that In step 5, the water conservation curing temperature is 25 to 80° C. and the time is 7 to 14 days.

Citation Information

Patent Citations

  • River-lake sludge-based unfired ultralight ceramsite, preparation method and application thereof

    CN110862252A

  • Light solid waste unfired ceramsite and preparation method thereof

    CN111362607A

  • Unfired fly ash ceramsite prefabricated ecological bank protection structure and preparation method thereof

    CN111499306A

  • Preparation method of ceramsite by using river sediment as raw material

    CN113105169A

  • Solid waste-based unfired high-strength ceramsite and preparation method thereof

    CN113200731A